Facilitators and barriers to implementing shared decision making: A cross-sectional study of physicians in Japan. Issue 7 (July 2022) - Koyama, Teruchika; Nawa, Nobutoshi; Itsui, Yasuhiro; Okada, Eriko; Fujiwara, Takeo
Highlights: This study analysed the facilitators and barriers to self-reported implementation of SDM among Japanese physicians in Japan. We found that significant facilitators included physicians' attitude, injunctive norm, intention and habit. Significant barriers included physicians' unfavorable attitude, lack of self-efficacy, knowledge, salience and experience. The major facilitators and barriers varied according to hospital types and specialty of physicians. Time constraints were not a significant barrier to self-reported implementation of SDM among Japanese physicians in Japan. Abstract: Objective: Shared decision making (SDM) is a collaborative process in which patients and healthcare providers jointly make a medical decision. This cross-sectional study aimed to identify the facilitators and barriers to self-reported implementation of SDM in Japan, and to explore if there is effect modification by hospital types. Methods: A total of 129 physicians in Japan completed a questionnaire that asked about their perception of SDM based on SDM-Q-Doc and its facilitators and barriers, which corresponded to each construct of the integrated behavioral model (IBM). The association between facilitators and barriers and SDM-Q-doc score was assessed using linear regression analysis. Stratified analysis by hospital types was also performed. Results: Significant facilitators included physicians' attitude, injunctive norm, intention and habit. Significant barriers included physicians' unfavorable attitude, lack of self-efficacy, knowledge, salience and experience. Moreover, experiential attitude (concerning patient characteristics), injunctive norm (concerning patient preferences), and physician's habit were significant facilitators for physicians working in university hospitals when compared to those working in municipal hospitals. Conclusion: The facilitators and barriers to implementing SDM in Japan were identified. Practice implications: More opportunities for training on SDM are needed to provide knowledge and skills, which will enhance salience and contribute their habitual practice.